The effect of proposed training units for developing balance on improving shooting accuracy among youth soccer players (aged 13-15) - saadsaoud, Fouad (sports creativity, 2025)
The technique of shooting towards the goal in football is considered the most important technique of practice in this game, witch distinguishes it form other sports, it is one of the essential means to get scores, which require the gathering of several components ; from fitness during performance, speed in implementation end power during shooting. As movement become more precise, it depends on balance which is very important to achieve that, as whenever the footballer keeps his/her balance during the performance of the movement, he can make it perfectly. from that point this designs to put an integrated training sessions for balance to determine the impact of balance as to improve the accuracy of shooting and also try to understand the confusion about the effectiveness of precision in shooting that mainly due the ability to balance. These proposed sessions have contributed in some extent in the raising of footballer’s balance ability which accompanied with a clear improvement in shooting towards goal and although it is far from the précised results of the tests that have been done, but it makes an obvious difference in the group which benefit from the integrated warming up training sessions. So that , the obtained results were in favor of the group which get the integrated training sessions in the test of shooting by foot and that aimed to measure the accuracy shooting. And also, It caused a clear difference in the measurement of the ability of balance in each of « flamingo’s test for fixed balance and motor balance ». witch indicate a clear improvement. Also that results demonstrate the need to improve the ability of balance in order to access the precision of shooting of the footballer, so that the groups which have undergone the experience ; despite what it realized, clear difference. In fact its results as we mentioned previously still keep away from the precise results of the tests. The thing that open the door to other studies which can benefit from our research to a comprehensive and brooder research take in to account all the factors that can include to determine the accuracy of footballers shooting. Try to disseminate the outputs of the largest possible segments of this age group witch has became a golden age for the development of skills and special abilities , thus increasing of skills and technique of the Algerian footballer youth